STUDENT’S LEARNING EXPERIENCE IN THE UTILIZATION OF ZOOM AND MICROSOFT TEAMS IN ONLINE LEARNING SETTING - Marisca Revani Putri; Venansia Ajeng S. A. Pedo; Norma Pawestri (E-LINK JOURNAL, 2021)
Teachers around the world currently struggled to find the most suitable learning tools and learning models to be implemented in the online classroom setting. Limited time and low attention span in online setting triggered teachers to set strategies to ensure the students experienced effective and rich learning process. One of the strategies to provide the effective learning experience was by utilizing technological tools. This research aimed to investigate the utilization of Zoom in synchronous sessions and Microsoft Teams during the asynchronous sessions. Experimental research design was implemented. 323 students from various majors in 11 classes were observed. E-questionnaire, video observation, pre/post-test, and students learning results were examined. Findings showed that experimental group students had better learning-experiences on interaction, knowledge test result, project result, critical thinking output, technological tools exposure, and student’s engagement during the synchronous sessions.